Community Perception And Motivation Analysis Of Implementing The Covid-19 Vaccination In Banjarejo Village, Ngadiluwih District Kediri - Siti Mariatus Sholika; Ema Mayasari (Universitas STRADA Indonesia, 2022)
Lack of understanding from the public and minimal information related to COVID-19 vaccination will make people have wrong perceptions and lack of motivation in carrying out COVID-19 vaccinations. The aim of this study was to determine the perception and motivation of the community towards the action of carrying out the Covid-19 vaccination in Banjarejo Village, Ngadiluwih District, Kediri Regency.This study designusing thecross-sectional, the population and sample of this study were 780 respondents with the Cluster Random Sampling technique so that 264 respondents were obtained. This data collection tool uses a questionnaire.The dataanalyzedusing Logistic Regression Test. the results of the study showed that (p = 0.000 < 0.005) there was a significant influence between people's perceptions and motivations for the act of carrying out the covid-19 vaccination.It is important to provide information and motivation to the public in order to create positive perceptions and motivation in carrying out the covid-19 vaccination.